2005
DOI: 10.1002/ejlt.200401122
|View full text |Cite
|
Sign up to set email alerts
|

Downstream processing of mannosylerythritol lipids produced by Pseudozyma aphidis

Abstract: Downstream processing of mannosylerythritol lipids produced by Pseudozyma aphidisPseudozyma aphidis DSM 14930 was used for the bioreactor production of mannosylerythritol lipids (MEL). A scheme is presented for the isolation and purification of MEL by using different solvents. Adsorption experiments of MEL at Amberlite XAD resins were performed. Up to 93% (wt-%) MEL could be transferred from the culture suspension into a newly formed, highly viscous solid phase by heating the culture suspension to !100 7C. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 20 publications
2
38
0
2
Order By: Relevance
“…Solvent extraction, adsorption on diVerent types of Amberlite XAD followed by solvent extraction and heating the culture suspension to 110°C for 10 min were the three downstream methods reported. The last method gave the highest yield of 93 wt% with a purity of 87 wt%, whereas the solvent extraction method gave only 79 wt% yield with 100 wt% purity [56]. …”
Section: Microbial Production Conditionmentioning
confidence: 99%
See 3 more Smart Citations
“…Solvent extraction, adsorption on diVerent types of Amberlite XAD followed by solvent extraction and heating the culture suspension to 110°C for 10 min were the three downstream methods reported. The last method gave the highest yield of 93 wt% with a purity of 87 wt%, whereas the solvent extraction method gave only 79 wt% yield with 100 wt% purity [56]. …”
Section: Microbial Production Conditionmentioning
confidence: 99%
“…Rau et al [56] reported the production of MEL in a bioreactor and the various downstream processing strategies for its recovery and puriWcation. Solvent extraction, adsorption on diVerent types of Amberlite XAD followed by solvent extraction and heating the culture suspension to 110°C for 10 min were the three downstream methods reported.…”
Section: Microbial Production Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oliveira et al 25 Whang et al 26 Jadhav et al 27 Christova et al 28 Gudiña et al 29 Glucolipid 73 Hewald et al 74 Rau et al 75 Fukuoka et al 76 Morita et al 77 Morita et al 78 Mannosylribitol lipid and mannosylarabitol lipid…”
mentioning
confidence: 98%